2017
DOI: 10.1039/c6ra25009b
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and characterization of electrospun feather keratin/poly(vinyl alcohol) composite nanofibers

Abstract: We have fabricated random and aligned feather keratin (FK)/PVA composite nanofibers through an electrospinning process. The morphology, molecular interactions, crystallization behavior, and tensile properties of the nanofibers were investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
39
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 40 publications
5
39
0
Order By: Relevance
“…Kakroodi et al 54 showed that adding a biopolymer such as cellulose leads to increasing tensile modulus and strength of PVA. Also Ming He et al 55 reported increasing keratin amount in PVA solution leads to increasing tensile strength from 5.59 to 6.71 MPa that is close to our results. Choo et al 56 showed that the tensile strength is enhanced with an increase in PVA/CS mass ratio, which could be attributed to intermolecular interactions caused by the hydrogen bonds between hydroxyl oxygen atoms in PVA and NH 2 or OH groups in CS.…”
Section: Tensile Strengthsupporting
confidence: 92%
See 1 more Smart Citation
“…Kakroodi et al 54 showed that adding a biopolymer such as cellulose leads to increasing tensile modulus and strength of PVA. Also Ming He et al 55 reported increasing keratin amount in PVA solution leads to increasing tensile strength from 5.59 to 6.71 MPa that is close to our results. Choo et al 56 showed that the tensile strength is enhanced with an increase in PVA/CS mass ratio, which could be attributed to intermolecular interactions caused by the hydrogen bonds between hydroxyl oxygen atoms in PVA and NH 2 or OH groups in CS.…”
Section: Tensile Strengthsupporting
confidence: 92%
“…showed that adding a biopolymer such as cellulose leads to increasing tensile modulus and strength of PVA. Also Ming He et al . reported increasing keratin amount in PVA solution leads to increasing tensile strength from 5.59 to 6.71 MPa that is close to our results.…”
Section: Resultsmentioning
confidence: 99%
“…The % crystallinity of CF was found to be 24. This fact is supported by earlier research [36]. From the fig.…”
Section: Xrd Analysis Of Nanofibersupporting
confidence: 87%
“…The FTIRspectra of the nanofiber samples were recorded with an infrared spectrometer using Agilent Technologies 6000 series for a wavenumber from 4000 to 650 cm -1 (Ming He et al,2017).…”
Section: Fourier Transform Infra Red (Ftir)mentioning
confidence: 99%
“…The amide I band is known to be especially sensitive to any conformational changes in the secondary structure of proteins [33]. Thus, the absorption bands of the amide I band are shown in Figure 4, where the predominant absorption band at ≈1650 cm −1 is characteristic of the α-helical structure, and the bands between 1610-1633 cm −1 and 1675-1695 cm −1 can be attributed to β-sheet and β-turn structures, respectively [26,36,37]. The calculated peak areas of the corresponding structures are summarized in Table 1.…”
Section: Ftir Spectroscopymentioning
confidence: 99%